FORMULASI PRODUK MINUMAN PROBIOTIK (YOGHURT) DARI SARI JAGUNG MANIS (Zea mays L.) DENGAN PENAMBAHAN BAKTERI PROBIOTIK Lactobacillus bulgaricus DAN Streptococcus thermophilus - Soni Muhsinin (Universitas Bhakti Kencana, 2016)
To prepare sweet corn probiotic beverage (Yoghurt) will be required Lactobacillus bulgaricus and Streptococcus thermophilus. The purpose of the is research is to produce probiotic beverage (Yoghurt) containing sweet corn base on the Indonesia National Standard (SNI), which has the antimicrobial activity and a good taste and a good preparations that can be accepted by society. The evaluation used were the analysis of antimicrobial activity and Indonesia National Standard (SNI) for analysis of sweet corn extract which includes water content analysis, total sugar analysis, and the ash content analysis. Meanwhile, the sweet corn probiotic beverage (Yoghurt) evaluation were analysis of lactic acid level, pH, viscosity, total LAB, protein, levels of fats, fondness, and total sugar. While Hedonic test showed the best formula was formula II (25% of the sweet corn), with 0,78% of lactic acid, pH 3,85, viscosity 236,7 cP, total LAB 10,0 Ã— 107 cfu/mL, 4,467% protein, 2,12% fats, 13,42% total sugar. While antimicrobial activity towards Salmonella typhi was 9,567 mm Â± 0,65. Thus, it can be cloncuded than the product complied with the requirments of Indonesia National Standard (SNI) except for the fats content.